2020
DOI: 10.1097/pr9.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a behavioral medicine approach in physiotherapy for patients with musculoskeletal pain: a scoping review

Abstract: Supplemental Digital Content is Available in the Text. The interventions in the scoping review were in agreement with the definition of behavioral medicine in physiotherapy, but reported behavior change techniques were few.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 59 publications
0
17
0
2
Order By: Relevance
“…The frequently reported component was to improve self-efficacy. The long-term follow-ups mostly showed positive effects, for example, reduction of fear and catastrophising, change in pain beliefs, increase in activities and pain SM strategies, and improved stress management (Soderlund et al 2020 ). The findings of the study suggest that factors like self-efficacy, depression, pain catastrophising and physical activity impact on outcomes of the SM programmes.…”
Section: Self-management: the Current State Of Evidencementioning
confidence: 99%
“…The frequently reported component was to improve self-efficacy. The long-term follow-ups mostly showed positive effects, for example, reduction of fear and catastrophising, change in pain beliefs, increase in activities and pain SM strategies, and improved stress management (Soderlund et al 2020 ). The findings of the study suggest that factors like self-efficacy, depression, pain catastrophising and physical activity impact on outcomes of the SM programmes.…”
Section: Self-management: the Current State Of Evidencementioning
confidence: 99%
“…However, matching intervention components with the definition of the biopsychosocial model of pain was somewhat difficult due to the overlap between components/aspects to be integrated into the assessment, treatment, and evaluation of patients with musculoskeletal pain. Two other reviews also reported similar results in which it was not possible to identify how the cognitive-behavioural and emotional components used in treatments and evaluations were operationalized [ 34 , 35 ]. This result highlights the importance of future studies to know how to effectively integrate the “cognitive, behavioural, and emotional components” in the management of musculoskeletal pain with a biopsychosocial theoretical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Andere Studien zeigen außerdem, dass PT bisher nur eine geringe Anzahl von Techniken zu Verhaltensänderung anwenden [19]. Dennoch erweisen sich physiotherapeutische Interventionen zur Verhaltensänderung langfristig als erfolgreich [18].…”
Section: Barrieren Für Bzlvunclassified
“…Zum anderen verwenden PT bislang nur wenige Techniken, um Verhaltensänderungen zu fördern [15]. Ebenso erweist sich die Studienlage hinsichtlich der Effektivität der Interventionen und zugrundeliegender Theorien als heterogen [16][17][18]. Für in Deutschland tätige PT wird ebenfalls vermutet, dass diese mehr Kompetenzen benötigen, um Verhaltensänderungen bei Patient*innen zu unterstützen [19].…”
Section: Introductionunclassified